REFLECTIONS IN A CONFLUENCE: A POSTCOLONIAL STUDY OF CROSS-BORDERING BONDAGE IN SOUTH ASIAN LITERATURE (Contemporary Journal of Social Science Review, 2025)
Saadat Manto is considered to be a strong pillar of post-independence literature and critiqued the independence and aftermaths. Manto is seen a revolutionary short stories writer who brought revolution in the context of decolonial context, resulted barbarism, savagism, killings, looting, robbing and rapping. The realistic approaches of Manto‘s stories are very haphazard and terrifying, affecting the minds of the readers. Explicitly, Manto is revolutionist but on the other hand Manto goes for harmonized, homogenous and cross-bordering bondage despite decolonization. Therefore, the current research deals with the selected short stories of Saadat Manto which are included in the delimitation of the current research. The research is qualitative and exploratory in nature that reflects the elements and issues of cross- bordering bondages which are very important steps towards peace and harmony. The researcher used Harish Trevidi and Sara Sulari‘s theoretical perspective to endorse the standpoint of the researcher. According to them South Asian literature is homogenous literary movement which is based on similar practices and regional practices which are no more different despite cross-bordering segregation. The research shows the elements of homogeneity and strong cross-bordering relationship which is the centre discussion of the research found at larger scale in Manto‘s selected short stories.